The Enigma of Endothelium in COVID-19 - Kaur, Savneet; Tripathi, Dinesh M.; Yadav, Angeera (Frontiers in Physiology, 2020)
Coronavirus disease 2019 (COVID-19) has emanated as one of the most brutal viral disease killing millions of people worldwide. With the aim of unearthing newer treatments, scientists all over the glove are striving hard to comprehend the underlying disease mechanisms of COVID-19. Several studies till date have indicated a dysregulated host immune response as the major cause of COVID-19 induced mortality. In this Perspective, we propose a key role of pulmonary endothelium in the pathogenesis of COVID-19. We draw parallels and divergences between COVID-19-induced respiratory distress and bacterial sepsis-induced lung injury and recommend the road ahead with respect to identification of endothelium-based biomarkers and plausible treatments for COVID-19.